Influences of Environmental Quality and safety & security on the Liveability of Residential Complexes in Erbil City - Maysa Ghazi Thanoon; Hamid Turki Haykal (Zanco Journal of Pure and Applied Sciences, 2021)
Liveability is a place based theory that makes the city a great place to live, it seeks to plan our living communities to promote good health, support the social cohesion and create safe and secure environment for the residents. This research seeks to examine the influence of two factors on liveability; the environmental quality and safety & security and their related issues. Five residential complexes implemented by the investment sector and located in different geographic locations in Erbil city are chosen as case study samples. The study employs an interrelated measuring tool by using spatial analysis check list and questionnaire survey with the residents. Results of the statistical analysis showed that significant differences were found between the residents satisfaction about their living environment in term of the studied factors, while non-significant differences were found between the results of both measuring tools used.